Comparative Content, Biological and Anticancer Activities of Heracleum humile Extracts Obtained by Ultrasound‐Assisted Extraction Method. Issue 7 (15th June 2022) - Ocal, Mustafa; Altunoglu, Yasemin Celik; Angeloni, Simone; Mustafa, Ahmed M.; Caprioli, Giovanni; Zengin, Gokhan; Paksoy, Mehmet Yavuz; Baloglu, Mehmet Cengiz
Abstract: As the safety and effectiveness of synthetic drugs remain in doubt, researchers are trying to develop natural medicines from medicinal plants. Herein, ethyl acetate, methanol and water extracts from the Heracleum humile plant were obtained by an ultrasonic‐assisted extraction process and the aim was to evaluate some biological effects of the extracts due to the limited data on the pharmacological properties of Heracleum humile in the literature. Weak antibacterial activity was observed on tested bacterial species. The minimum inhibitory concentration and the minimum bactericidal concentration values ranged from 250 to 500 μg/mL. In addition, cytotoxic activity was determined using the MTT test. The strongest findings were determined for ethyl acetate extract on the MDA‐MB‐231 cell lines at the 48 th  hour (IC50 :97.94 μg/mL), followed by the MCF‐7 cell lines at the 24 th  hour (IC50 :103.9 μg/mL). All extracts of Heracleum humile contained mainly flavonoids, phenolic acids and their derivatives, i. e., well‐known compounds that possess numerous biological activities such as antioxidant, anti‐inflammatory, anticancer, antimicrobial etc. The study results could provide important information that Heracleum humile could be a potential candidate as a natural enzyme inhibitor. It can be concluded that these extracts could be useful in the elementary step of improving novel plant‐derived multifunctional pharmaceuticals. Abstract :